Rapid single-molecule characterisation of enzymes involved in nucleic-acid metabolism. Issue 1 (2nd November 2022) - Mueller, Stefan H; Fitschen, Lucy J; Shirbini, Afnan; Hamdan, Samir M; Spenkelink, Lisanne M; van Oijen, Antoine M
Abstract: The activity of enzymes is traditionally characterised through bulk-phase biochemical methods that only report on population averages. Single-molecule methods are advantageous in elucidating kinetic and population heterogeneity but are often complicated, time consuming, and lack statistical power. We present a highly-generalisable and high-throughput single-molecule assay to rapidly characterise proteins involved in DNA metabolism. The assay exclusively relies on changes in total fluorescence intensity of surface-immobilised DNA templates as a result of DNA synthesis, unwinding or digestion. Combined with an automated data-analysis pipeline, our method provides enzymatic activity data of thousands of molecules in less than an hour. We demonstrate our method by characterising three fundamentally different enzyme activities: digestion by the phage λ exonuclease, synthesis by the phage Phi29 polymerase, and unwinding by the E. coli UvrD helicase. We observe the previously unknown activity of the UvrD helicase to remove neutravidin bound to 5′-, but not 3′-ends of biotinylated DNA.